Potential of Akkermansia muciniphila and its outer membrane proteins as therapeutic targets for neuropsychological diseases - Zhang, Fenghua; Wang, Dali (Frontiers in Microbiology, 2023)
The gut microbiota varies dramatically among individuals, and changes over time within the same individual, due to diversities in genetic backgrounds, diet, nutrient supplementations and use of antibiotics. Up until now, studies on dysbiosis of microbiota have expanded to a wider range of diseases, with Akkermansia muciniphila at the cross spot of many of these diseases. A. muciniphila is a Gram-negative bacterium that produces short-chain fatty acids (SCFAs), and Amuc_1100 is one of its most highly expressed outer membrane proteins. This review aims to summarize current knowledge on correlations between A. muciniphila and involved neuropsychological diseases published in the last decade, with a focus on the potential of this bacterium and its outer membrane proteins as therapeutic targets for these diseases, on the basis of evidence accumulated from animal and clinical studies, as well as mechanisms of action from peripheral to central nervous system (CNS).